Towards an Understanding of health and physical education (Fiep Bulletin - online, 2015)
The world literature on physical education was very much enriched with the publication of this excellent illustrated book of 376 pages written by Professor Emeritus of Physiology at the “George Williams College” in the U.S.A., Arthur H. Steinhaus.